Innovating Disaster Risk Reduction (DRR) Framework for Ensuring Urban Resilience: A Study on Coastal Delta Cities - Adnan, Md Sarfaraz Gani (Journal of Bangladesh Institute of Planners, 2015)
Coastal delta cities are at risk to hydro meteorological hazards especially from flooding. To reduce this risk many cities have built extensive flood defence system that can only reduce the probability of flood occurrence. So, the study is focusing on developing a framework for selecting the most suitable flood risk reduction policies according to the local situation which will ensure resilience. First, from the physical and environmental point of view 10 DRR policies have been identified under three broad approaches based on the DRR initiatives by eleven precedent (model) cities. After that few explanatory variables are selected on the basis of geography, climate, flood hazard, risk magnitude and economic aspects. Then a correlation has been established among DRR policies and explanatory variables and then the pattern of correlations have been explained. The findings of this study show a framework from where appropriate DRR policies can be selected. It has been observed that in a stable political situation, a city can decide to adopt various DRR policies based on geography and climate, hazard pattern, magnitude and experience. The study further reveals that along with structural flood protection, practicing environmental and planning management can reduce the flood risk in coastal cities. Journal of Bangladesh Institute of Planners, Vol. 8, Dec 2015, pp. 123-134